Enumeration of typical plans of multifactorial experiment - Костенко, Е. М. (Scientific Progress & Innovations, 2013)
The method of multifactorial experiment of typical plans enumeration, based on representation of MFE plans in the form of serial sequences is offered. The decision of stage-by-stage problems of the method is considered. Properties of plans of MFE serial sequences are investigated, estimations of their quantity are received, and procedure of base serial sequences set formation and typical variants of plans of MFE structures is described. Examples of optimum plans of MFE catalogues are resulted. Application of the offered method will allow to simplify the process of choice of minimal plans of MFE for a plenty of factors.